Text mining in career studies: generating insights from unstructured textual data - Kobayashi, Vladimer B. (Handbooks of Research Methods in Management series, 2021)
This Handbook of Research Methods in Careers serves as a comprehensive guide to the methodologies that researchers use in career scholarship. Presenting detailed overviews of methodologies, contributors offer numerous actionable best practices, realistic previews, and cautionary tales based on their vast collective experience of research in the discipline.